PENGARUH SISTEM AKUNTANSI KEUANGAN DAERAH DAN SISTEM PENGENDALIAN INTERN TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH KOTA PAREPARE - Pitra Amalia, Dian; Muchran, Muchriana; Nasrun, Muhammad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The implementation of the Regional Financial Accounting System (SAKD) and the Internal Control System (SPIP) in managing government financial reports is crucial. Government financial reports must meet qualitative characteristics: relevance, reliability, comparability, and understandability. This study aims to examine the influence of the Regional Financial Accounting System and the Internal Control System on the Quality of Government Financial Reports at the Parepare City Regional Finance Agency (BKD). This study employed a quantitative approach using a survey method. The population consisted of employees at the Parepare City Regional Finance Agency, with a purposive sampling method yielding 36 respondents directly involved in financial management. Data were collected through questionnaires and analyzed using multiple linear regression with SPSS 26. The results indicate that: (1) the Regional Financial Accounting System has a positive and significant effect on the Quality of Government Financial Reports; (2) the Internal Control System has a positive and significant effect on the Quality of Government Financial Reports; and (3) simultaneously, the Regional Financial Accounting System and the Internal Control System have a positive and significant effect on the Quality of Government Financial Reports at the Parepare City Government. These findings confirm that a well-implemented accounting system and robust internal controls are essential determinants of high-quality governmental financial reporting.